TIKTOK AS A TOOL OF AUTONOMOUS LEARNING: INDONESIAN EFL STUDENTS’ VOICES - Hadijah Hadijah; Ulfa Widayati; Takdir Ilahi; Ema Puspitasari (Universitas Wiralodra, 2023)
This research aims to know the students’ perspective on TikTok as a tool for autonomous learners. The researcher used a qualitative case study approach with five voluntarily participating students of the English department of Institut Agama Islam Darul A’mal Lampung as the participants. An in-depth semi-structured interview was applied as the data collection technique. The theme-based analysis was used in this study. The finding showed that 1) TikTok was good to improve the students speaking ability by providing access to a variety of educational videos, which can teach students different pronunciation and phrases; 2) TikTok motivated students to learn the English language. TikTok has helped students with learning English. It's an entertaining way to practice their pronunciation and listening comprehension skills, so they can get a better understanding of different cultures. It helps them stay motivated to continue learning English; 3) TikTok encourages students to learn grammar by watching video clips of native speakers about grammar topics, such as filling in the blanks and completing sentences, joining a study group, or challenging for feedback from peers. However, the researcher found the negative aspect include being exposed to inappropriate content, and the content on TikTok tends to move along quickly.